Kepentingan Vietnam Dalam Konflik Laut China Selatan - Dwi Jaya, I Gede Made (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT The Purpose of this research is to explain the national interest of Vietnam on the South East China Conflict. Vietnam was the one of the countries that involved in South China Sea dispute since mid-20 century. Vietnam also was the country that be the most vocal country on claiming upon the island especially spartly and paracel. This is based on its importance to the region because this region is the  busiest shipping lanes and it is expected to have a lot of energy content. In this condition, Vietnam want to pursue its interest in this region especially the energy resource. In this case, I put more emphasis on the interest and efforts by Vietnam on pursuing their goal. Keywords : conflict, interest, energy